ANALISA PENDAPATAN USAHA NELAYAN PERAHU MOTOR DI DESA SELUBUK KECAMATAN AIR NAPAL KABUPATEN BENGKULU UTARA - Sumantri, Bambang; Suwarli, Bian (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
Fishery sector represent very important sector to be developed beside agricultural sector of ranch and food crop. Development in fishery sector to date remain to be aimed at a contribution improvement sub of fishery sector in guaranting available of protein hewani food substance, industrial raw material, improvement export, pushing opportunity and employment extension try, increased fisherman earnings and also support area development. this Spacious college aim to to know mean earnings accepted by speed boat fisherman. activity college field executed in Countryside of Deep Hollow of Subdistrict Irrigate Napal Regency North Bengkulu. Analysis Method used is earnings analysis. Result college field indicate that earnings flatten to flatten month fisherman of speed boat is Rp1.586.001,00. This Circumstance mirror that individualness earnings accepted by fisherman a high relative.